The discourse of drag queen story time challengers and supporters: A case study from the Okanagan Regional Library - Chabot, Roger; Helkenberg, Davin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
Drag Queen Story Time (DQST) is a public library program where drag queens lead a story time for children and families. Although this program is meant to celebrate diversity, the program can also invite an onslaught of political warfare against gender and sexuality nonconformity and intellectual freedom. This study analyzes the arguments of DQST challengers and supporters to better understand the motivations behind both negative and positive responses to this polarizing program. The study examines 406 publicly available letters written by community members, professionals, and vested organizations expressing opposition or support for a DQST that was hosted in a large library system in Canada, the Okanagan Regional Library (ORL) in 2019.